Achieving structural anisotropy of liquid crystalline epoxy by manipulation with crosslinking parameters - M. Kisiel; B. Mossety-Leszczak; B. Strachota; A. Strachota (eXPRESS Polymer Letters)
The article presents a detailed study of the curing process of liquid crystalline epoxy resin focused on selecting optimal crosslinking conditions allowing to achieve a highly anisotropic product. By the manipulation of time, temperature, and applied magnetic induction during the chemical reaction, leading to the formation of neat epoxy and carbon-epoxy composite, the desired conclusions were developed. During X-ray analysis, it was established that the most anisotropic network is created when the following parameters are chosen: low curing temperature, short time of curing, and high magnetic induction. These conditions, however, do not allow to synthesize fully cured products, so the two-stage process was proposed, which slightly deteriorates the level of anisotropy, giving maximum conversion in return. The level of order is described with a dependent on the intensity of peaks present on the X-ray scattering plots parameter called the orientation function OF. The introduction of a graphite-like nanofiller generally slightly decreases the anisotropy of the polymer network. The main finding of this article is the optimized process of curing, allowing to obtain highly anisotropic material. This optimization shows tendencies between material ordering and curing properties, so it can be useful in future studies allowing to reach optimal conditions a lot faster.